Decoupled linear load flow for contingency analysis / Noraniza Mohamad Yusof - Mohamad Yusof, Noraniza (1996)
The load flow problem can be defined as the calculation of the real and reactive powers flowing in each line and the magnitude and phase angle of the voltage at each bus of a given transmission system for specified generation and load conditions. The information obtained from the load-flow studies can be used to test the system's capability to transfer energy from generation to load without overloading lines and to determine the adequacy of voltage regulation by shunt capacitors, shunt reactors, tap-changing transformers, and the var-supplying capability of rotating machines.